Quercetin Attenuates Osteoporosis in Orchiectomy Mice by Regulating Glucose and Lipid Metabolism via the GPRC6A/AMPK/mTOR Signaling Pathway - Sun, Jie; Pan, Yalan; Li, Xiaofeng; Wang, Lining; Liu, Mengmin; Tu, Pengcheng; Wu, Chengjie; Xiao, Jirimutu; Han, Qiuge; Da, Weiwei; Ma, Yong; Guo, Yang (Frontiers in Endocrinology, 2022)
Objective: This study aimed to elucidate the role of quercetin in androgen deprivation therapy-induced osteoporosis in mice. Methods: C57BL/6 mice were subjected to orchiectomy and quercetin (75 and 150 mg/kg/d) interventions were carried out for 8 weeks. Micro-computed tomography was used to evaluate the bone microstructure, and a three-point bending test was used to evaluate the biomechanical parameters. Hematoxylin and eosin (H&E) staining was used to observe the shape of the distal femur, gastrocnemius muscle, and liver. The balance motion ability in mice was evaluated by gait analysis, and changes in the gastrocnemius muscle were observed via Oil red O and Masson’s staining. ELISA and biochemical analyses were used to assess markers of the bone, glucose, and lipid metabolism. Western blotting analyses of glucose and lipid metabolism-related protein expression was performed, and expression of the GPCR6A/AMPK/mTOR signaling pathway-related proteins was also assessed. Results: After 8 weeks of quercetin intervention, quercetin-treated mice had increased bone mass, bone strength, and improved bone microstructure. Additionally, gait analysis, including stride length and frequency, were significantly increased, and the stride length CV and gait symmetry was correspondingly reduced. H&E staining of the gastrocnemius muscle showed that the cross-sectional area of the myofibers had increased significantly, suggesting that quercetin improves balance, motion ability, and muscle mass. In terms of improving bone metabolism, serum levels of insulin, triglycerides, total cholesterol, and low-density lipoprotein were decreased, and those of insulin-like growth factor-1 and high-density lipoprotein were increased after quercetin intervention. Expression of proteins involved in glucose uptake was increased, whereas that of proteins involved in lipid production was decreased. Moreover, the GPRC6A and the p-AMPK/AMPK expression ratio was elevated in the liver and tibia tissues. In contrast, the p-mTOR/mTOR ratio was reduced in the low- and high-quercetin groups. Conclusion: These findings indicate that quercetin was potent against osteoporosis induced by testosterone deficiency, and its beneficial effects might be associated with the regulation of glucose metabolism and inhibition of lipid metabolism via the GPCR6A/AMPK/mTOR signaling pathway.